Genre-Based Approach and Digital Flashcard: Enhancing Pre-service English Teacher Students’ Speaking Capability - Ramadhan, Rizki; Dibdyaningsih, Haris; Sudarso, Hendra (IJET (Indonesian Journal of English Teaching), 2022)
In 2020, the Ministry of Education and Culture of Indonesia published the newest curriculum, Kurikulum Merdeka, which demands EFL teachers implement a genre-based approach during teaching and learning. In response to this call, this research aimed to investigate the implementation of a genre-based approach to enhance EFL pre-service English teacher students’ speaking ability. This research employed classroom action research to investigate whether the approach could improve students’ speaking ability. This research was conducted at STKIP Al Hikmah Surabaya, and the participants of the research were selected through purposive sampling. In order to answer the research questions, the researcher used a post-test, an interview, a questionnaire, and an observation as data collection techniques. Furthermore, the interactive data analysis model proposed by Miles and Huberman was implemented to analyze the data. The study concluded that the genre-based approach can improve EFL pre-service English teacher students' capability in speaking. The pre-service English teacher students’ significant enhancement in their speaking capability is exhibited by the generic structure of the descriptive text, such as the social function, the organization, and grammatical features. All informants could fulfill relatively all parts, which is fundamental to composing a descriptive text.